Increasing Vocabulary Acquisition and Retention in EFL Young Learners through the Use of Multimodal Texts (Memes) - Aedo, Pablo; Millafilo, Claudia (Colombian Applied Linguistics Journal, 2022)
This research assessed the use of multimodal texts for vocabulary acquisition and retention of 18 EFL young learners from 6th grade aged between 11 and 12 years and enrolled in a primary school in Chile. The multimodal texts (memes) were designed by the researchers and selected to meet different criteria in terms of vocabulary. To gather information, three vocabulary tests were administered: before, right after, and two weeks after the end of the intervention. The data from the tests were analyzed with descriptive statistics, while the focus groups were interpreted with the content analysis technique. The results reveal an increase in the acquisition and retention of the selected vocabulary. Furthermore, the focus group conducted with the students shows that young learners value the acquisition of English as a foreign language, especially through the use of vocabulary. Finally, the use of multimodal texts in the classroom is perceived by students as an innovative and fun way to learn.